THE LITERARY LEGACY OF KALLISTOS ANGELIKOUDES: AN ATTEMPT AT SYSTEMATIZATION - RODIONOV, Oleg (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
This article explores the little studied and partially unpublished literary corpus of Kallistos Angelikoudes, one of the most fascinating late Byzantine hesychast authors. It addresses some of the problems associated with the manuscript tradition of his writings and offers a new approach to the systematization of his oeuvre. Despite the uncertainty regarding the identification of the two groups of texts that make up the books of Angelikoudes’ literary corpus, that is, the Hesychastic Education and the Hesychastic Consolation, this article advances an argument with regard to the possible composition of these works.